Synthesis and Characterization of Chitosan/Urea-Formaldehyde Hollow Resin for Metal Ion Removal - Y. Abdelaal, Magdy; O.S. Bahaffi, Saleh; H. El-Sayed, Nadia (Asian Journal of Chemistry, 2014)
In the current study, a series of hollow resins has been synthesized by using chitosan succinate and urea-formaldehyde resin as a cage resin to prepare new polychelates for different metal ions. Resins were characterized by FT-IR spectroscopy, thermal analysis and scanning electron microscopy. Resins have also been investigated for the removal of metal ions from their aqueous solutions through the formation of polychelates of the metal ions and their sorption capacity of such metal ions was determined. The hollow resin exhibited higher surface area than its separate components which facilitates higher ion uptake of metal ions from aqueous solutions.